Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 238749 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Zelkova Spach", "TaxonKey is Toona (Endl.) M.Roem.", "TaxonKey is Ulmus L.", "TaxonKey is Umbellularia Nutt.", "TaxonKey is Zanthoxylum L.", "TaxonKey is Tilia L.", "TaxonKey is Styrax L.", "TaxonKey is Zizyphus Adans., 1763", "TaxonKey is Tetracentron Oliv." ] }, "HasCoordinate is true" ] } The dataset includes 238749 records from 719 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000781-150221044754056/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences